Changes in dental status over 10 years in 80-year-old people: a prospective cohort study - Ha¨ma¨la¨inen P, Meurman JH, Keskinen M, Heikkinen E. (Blackwell Synergy, 2004)
The aim of the present study was to follow-up the condition of the teeth over a sufficiently long period.